(untitled) (El-Wahat Journal for Research and Studies, 2015)
The economic organization’s role in the current situation not only to pay attention to the internal ocean, but also to attention outside Ocean which features competition in accordance with the Court and studied the laws of betting by some especially the developed ones states, which requires economic institution need to differentiate its products from its competitors through attention to quality and that comes through the introduction of global standards represented in the standardization: ISO 14000, ISO: 9000 in order to improve their economic return and achieve their goals. Key words: quality, total quality, total quality management, environment, competition, profitability.